2010
DOI: 10.1038/mp.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic molecular and anatomical changes in the glucocorticoid receptor in human cortical development

Abstract: The glucocorticoid receptor (GR) has a critical role in determining the brain's capacity to respond to stress, and has been implicated in the pathogenesis of psychiatric illness. We hypothesized that key changes in cortical GR occur during adolescence and young adulthood, at a time when individuals are at increased risk of developing schizophrenia, bipolar disorder and major depression. We investigated the mRNA and protein expression of GR in the dorsolateral prefrontal cortex across seven developmental time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 77 publications
5
61
0
Order By: Relevance
“…The most prominent change was displayed by the as yet not fully defined 67 kDa GR immunoreactive band. In humans, changes in the expression of 67 kDa isoform have been associated with alterations in stress responsivity across the lifespan [42]. The variability in the expression pattern of GR isoforms in the rat hippocampus has been linked to the hyporesponsiveness of the neonatal HPA axis [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent change was displayed by the as yet not fully defined 67 kDa GR immunoreactive band. In humans, changes in the expression of 67 kDa isoform have been associated with alterations in stress responsivity across the lifespan [42]. The variability in the expression pattern of GR isoforms in the rat hippocampus has been linked to the hyporesponsiveness of the neonatal HPA axis [50].…”
Section: Discussionmentioning
confidence: 99%
“…different GR isoforms in the hippocampus. We employed the P-20 anti-GR antibody previously used to detect five GR isoforms in the human brain [42]. In the rat hippocampus, the anti-GR antibody detected four protein immunoreactive bands at 97, 67, 40 and 25 kDa.…”
Section: Eod Feeding Increased the Hippocampal Corticosterone Contentmentioning
confidence: 99%
“…The archetypal GR isoform, full-length GRa (B105 kDa), is expressed in the human prefrontal cortex, along with smaller GRa isoforms, approximately 67, 50, and 40 kDa in size (Sinclair et al, 2011). We have previously shown that the 50 and 40 kDa isoforms putatively represent the GRa-D1 and GRa-Dx isoforms, respectively (Sinclair et al, 2011), which arise from employment of alternate translation start sites in exon 2 (Lu and Cidlowski, 2005; Figure 1). However, it is not known whether other human GR isoforms such as GRb, GR-'A' (D5-7), GR-P, and GRg (Bamberger et al, 1995;Moalli et al, 1993;Rivers et al, 1999) are expressed in the prefrontal cortex.…”
Section: Introductionmentioning
confidence: 93%
“…Individual variability in these factors should always be taken into consideration, when analysing the AL model in schizophrenia. Similarly to neurodevelopmental model of schizophrenia, critical periods of brain development can be distinguished in the AL concept, when stress followed by the multisystem dysregulation may mediate the increased risk of schizophrenia in susceptible individuals (Bilbo and Schwarz, 2009;Miller et al, 2013a;Sinclair et al, 2011b).…”
Section: Allostatic Load Throughout the Lifespanmentioning
confidence: 98%
“…It has been shown that mRNA abnormalities may be partially due to the functional polymorphisms within the GR (NR3C1) gene (Sinclair et al, 2012). Interestingly, it has been shown that the neonatal and late adolescent periods represent critical windows of stress pathway development through cortical GR changes, as they are important for increased vulnerability to stress in the etiopathogenesis of schizophrenia (Sinclair et al, 2011b). Dynamic patterns of GR isoform expression in white matter astrocytes and pyramidal neurons across the development strengthens the hypothesis that windows of vulnerability to stress exist across human cortical development.…”
Section: The Hypothalamic-pituitary-adrenal (Hpa) Axismentioning
confidence: 99%